Influência da suplementação de tomate e licopeno na remodelação cardíaca após infarto agudo do miocárdio - Pereira, Bruna Letícia Buzati [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Heart failure is a common complication after the acute myocardial infaction (AMI), and cardiac remodeling has a prominent role in this scenario. Increased oxidative stress and inflammation are associated with cardiac remodeling after AMI. Due to the great economic and social and high mortality rates, it's important to identify other factors that modulate the process of cardiac remodeling and among this factors are the supplementation of foods with antioxidant properties, such as tomato (Lycopersicon esculentum), and of its primary constituents, the lycopene. Objectives: Evaluate the influence of tomato and lycopene supplementation in cardiac remodeling after AMI. Methods: Male Wistar rats, weighing between 200 and 250g, were submitted to the experimental infarction or sham surgery and divided into six groups: 1) Sham group (animals undergoing sham surgery) fed a standard diet (SC group); 2) Sham group fed diet supplemented with 1 mg lycopene/kg body/day (SL group); 3) Sham group fed diet supplemented with tomato (ST group); 4) infarcted group (animals submitted to experimental infarction) fed a standard diet (IC group); 5) infarcted group fed diet supplemented with 1 mg lycopene/kg of body weight/day (IL group); 6) infarcted group fed diet supplemented with tomato (IT group). The lycopene and the tomato were dilute in corn oil to be add into the diet (0.5 ml of corn oil/kg body weight/day) and the standard group received the same oil. After three months of observation the animals underwent functional, morphometric and biochemical analysis. The values were expressed as mean ± standard deviation. The variables that did not meet the criteria of normality and equal variance were normalized before analysis. Comparisons between groups were made by two-way analysis of variance (ANOVA). For non-normalized data, we used Kruskal-Wallis test (comparison between the Sham groups, SC, SL and ...

Introdução: A insuficiência cardíaca é uma frequente complicação após o infarto agudo do miocárido (IAM), sendo que a remodelação cardíaca apresenta papel de destaque nesse cenário. O aumento do estresse oxidativo e do processo inflamatório estão associados com a remodelação cardíaca após o IAM. Devido ao grande impacto sócio econômico e às altas taxas de mortalidade, torna-se relevante a identificação de outros fatores que modulem o processo de remodelação cardíaca e podemos destacar a suplementação de alimentos com propriedades antioxidantes, como o tomate (Lycopersicon esculentum), e um de seus principais constituintes, o licopeno. Objetivo: Avaliar a influência da suplementação de tomate e licopeno na remodelação cardíaca após o IAM. Materiais e métodos: Ratos Wistar machos, com peso entre 200 e 250g, foram submetidos ao infarto experimental ou à cirurgia simulada e alocados em seis grupos: 1) grupo Sham (animais submetidos à cirurgia simulada) alimentado com dieta padrão (grupo- SC); 2) grupo Sham alimentado com dieta suplementada com licopeno 1mg/kg peso corporal/dia (grupo-SL); 3) grupo Sham alimentado com dieta suplementada com tomate (grupo-ST); 4) grupo infartado (animais submetidos ao infarto experimental) alimentado com dieta padrão (grupo-IC); 5) grupo infartado alimentado com dieta suplementada com licopeno 1mg/kg de peso corporal/dia (grupo-IL); 6) grupo infartado alimentado com dieta suplementada com tomate (grupo-IT). O licopeno e o tomate das dietas foram diluídos em óleo de milho para serem adicionados à ração (0,5ml de óleo/kg de peso corporal/dia) e os grupos controles tiveram a mesma quantidade de óleo adicionado. Após três meses de observação os animais foram submetidos ao estudo funcional, morfométrico, e bioquímico. Os valores obtidos foram apresentados em média ± desvio padrão. As variáveis que não preencheram os critérios de normalidade e de...
Keywords: Cardiologia; Infarto do miocárdio; Stress oxidativo; Antioxidantes; Tomate; Myocardial infarction